Type 3 innate lymphoid cells maintain intestinal epithelial stem cells after tissue damage - Aparicio-Domingo, P; Romera-Hernandez, M; Karrich, J; Cornelissen, F; Papazian, N; Lindenbergh-Kortleve, D; Butler, J; Boon, L; Coles, M; Samsom, J; Cupedo, T (Rockefeller University Press, 2015)
Disruption of the intestinal epithelial barrier allows bacterial translocation and predisposes to destructive inflammation. To ensure proper barrier composition, crypt-residing stem cells continuously proliferate and replenish all intestinal epithelial cells within days. As a consequence of this high mitotic activity, mucosal surfaces are frequently targeted by anticancer therapies, leading to dose-limiting side effects. The cellular mechanisms that control tissue protection and mucosal healing in response to intestinal damage remain poorly understood. Type 3 innate lymphoid cells (ILC3s) are regulators of homeostasis and tissue responses to infection at mucosal surfaces. We now demonstrate that ILC3s are required for epithelial activation and proliferation in response to small intestinal tissue damage induced by the chemotherapeutic agent methotrexate. Multiple subsets of ILC3s are activated after intestinal tissue damage, and in the absence of ILC3s, epithelial activation is lost, correlating with increased pathology and severe damage to the intestinal crypts. Using ILC3-deficient Lgr5 reporter mice, we show that maintenance of intestinal stem cells after damage is severely impaired in the absence of ILC3s or the ILC3 signature cytokine IL-22. These data unveil a novel function of ILC3s in limiting tissue damage by preserving tissue-specific stem cells.